Koleksi Spesimen Round-skin Aves di Museum Zoologi Universitas Andalas Padang: Passerine - Muhammad Nazri Janra; Aadrean Aadrean; Heru Handika; Ahmad Mursyid (LOMBOK JOURNAL OF SCIENCE, 2020)
Since its establishment on 2004, Zoological Museum of Andalas University (MZUA) has been functioning as scientific institution, including deposition, maintaining and preserving vertebrate specimens in various forms. Round-skin technique for preserving avian specimen started to be used as preparation method since 2012, which brought novelty in learning its biological aspects. It provides more reliable taxonomical and molecular materials for future use, which was one of the endorsements for this technique. This article aimed to inventory the round-skin specimen of Passerines in MZUA by using descriptive method to examine their taxonomical and curatorial aspects. As many as 196 avian round-skin specimens have been catalogued until July 2016; 166 of them were from Passeriformes order (Passerines), belonged to 57 species and 14 families. Timaliidae was family with most members collected (67 individuals), followed respectively by Nectariniidae (20 individuals), Pycnonotidae (19 individuals), Muscicapidae (17 individuals), Turdidae (12 individuals) and mixed of other families (31 individuals). While the localities of collection were mostly centered on Central Region of Sumatra (i.e. West Sumatra, Jambi), a handful of specimens were collected from outside of the main island. A systematic effort to develop the collection and improve the representativeness of Sumatran avian species is continuously needed, not only to fulfill its scientific purpose, moreover to serve the conservation objective.